HUBUNGAN ANTARA KEMAMPUAN AFEKTIF DENGAN PRESTASI AKADEMIK MAHASISWA PROGRAM STUDI PENDIDIKAN GEOGRAFI FIS UNNES - Tukidi, Tukidi (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2014)
This study aims (1) to obtain information about the ability of student affectiveGeography Education Department, and (2) to find out the magnitude of therelationship between affective abilities with their academic achievement. Thisstudy is an evaluation research about affective skills, using the unit of analysisstudent geography education department FIS UNNES. The data collectionmethods used are: (1) questionnaire methods to obtain data on affective abilitiesand academic achievement, (2) documentation methods for obtaining data on thenumber and list of student. Data analysis techniques used were the percentageand descriptive techniques with descriptive statistic. Information obtained fromresearch that the ability of student affective Geography Education Departmentinclude high category, meaning that students have a positive attitude behavior.From the four sub variables affective capabilities, maintaining order andcleanliness of the campus occupies is the highest score. The test results indicatethat the ability of affective relationship with student academic achievement, it’smean that the higher or positive affective abilities of students to follow academicachievement.